Implementation of Innovation in the Reception of Candidate Members of the Republic of Indonesia State: JEL Classification: H83, J45, M51, D73, J24 - Syarifah Nur Fitri Yani; Muhammad Irvan Nur Iva; Rahayu Rahayu; Herman H. Dody (Journal La Bisecoman, 2026)
The competitive advantage of an organization is largely determined by the quality of its human resources. The recruitment and selection process is crucial for obtaining high-quality and competitive personnel. This study aims to analyze the implementation of innovations in the recruitment of Indonesian National Police (POLRI) members in the South Sulawesi Regional Police. This study uses a descriptive qualitative method. This research was conducted at the South Sulawesi Regional Police. The results of the study indicate that the implementation of innovations in the recruitment of Indonesian National Police members on individual factors, motivation is the main driver in the development and implementation of recruitment of Indonesian National Police members, the pattern of cooperative relationships creates a shared commitment in realizing the success of recruitment of Indonesian National Police members. Structural factors, cooperation has been strengthened through MoUs and the provision of honorariums as a form of appreciation, but there are still challenges such as limited cross-sector communication. Cultural factors, indicate that frequent changes in guidelines cause normative uncertainty and gaps between regulations and implementation.